Are serotonin metabolite levels related to bone mineral density in patients with neuroendocrine tumours?. (29th July 2013) - Sen Gupta, Piya; Grozinsky‐Glasberg, Simona; Drake, William M.; Akker, Scott A.; Perry, Les; Grossman, Ashley B.; Druce, Maralyn R.
Summary Background Bone mineral density (BMD) is influenced by multiple factors. Recent studies have highlighted a possible relationship between serotonin and BMD. Patients with neuroendocrine tumours (NETs) frequently have elevated urinary 5‐hydroxy‐indoleacetic acid (5‐HIAA) levels, a serotonin metabolite. Evaluation of the relationship between 5‐HIAA and BMD in patients with NETs may provide insights into the relationship between serotonin and BMD. Methods One‐year audit of consecutive patients with NETs within two institutions. Relationships between urinary 5‐HIAA and dual X‐ray absorptiometry (DEXA)‐scan‐measured BMD were investigated by group comparisons, correlation and regression. Results Of 65 patients with NETs, 19 did not participate or were excluded. Of 46 subjects evaluated (48·9% males, 63·8 ± 10·5 years, BMI 26·6 ± 4·4 kg/m2) with 32 gastrointestinal, 9 pancreatic, 3 pulmonary and 2 ovarian NETs, 72·3% had the carcinoid syndrome. Median interval from diagnosis was 4·0 years (IQR 2·0–6·0); 41·3% had osteoporosis and 32·6% osteopaenia (WHO definition). The group with a higher urinary 5‐HIAA had a lower hip BMD (total T‐score and Z‐score), confirmed on individual analysis (Spearman's rank correlation −0·41, P = 0·004; −0·44, P = 0·002, respectively); urinary 5‐HIAA was not found to be an independent predictor for BMD on multiple linear regression analysis. Conclusion These data of patients with NETs with higher serotonin metabolites having a lower BMD at the hip in group and individual comparisons, warrants further evaluation. Urinary 5‐HIAA measurement alone cannot be used to predict future BMD. A larger cohort with prospective design including fractures as a clinical outcome will aid these data in determining whether patients with NETs should be subject to targeted osteoporosis prevention.